SIMULTANEOUS PRICING AND LOT SIZING FOR A DETERIORATING PROCESS - Hari Prasetyo; Gusti Fauza (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2006)
This paper develops Banerjee’s model (2005), on concurrent pricing and lot sizing for a supplier on the bases of contractual agreement with a buyer, by considering condition that the supplier’s production system deteriorates over time/usage. Further, it is also assumed that the bargaining position of the buyer is stronger than that of the supplier so its economic lot size policy is used to determine the supplier’s production batch size (i.e. the supplier production batch size is an integer multiple of the buyer’s order quantity). The objective of the supplier here is to determine the product’s selling price, in conjunction with an appropriate lot size policy, to maximize targeted gross profit per unit. Any relevant costs considered by the supplier are setup cost, manufacturing cost, holding cost, restoration cost, and repairing cost. To solve the model, a simple algorithm is employed, and a numerical example using Banerjee’s parameter is implemented to illustrate the works of the model.